2000
DOI: 10.1007/s004250000279
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic apparatus organization and function in the wild type and a chlorophyll b -less mutant of Chlamydomonas reinhardtii . Dependence on carbon source

Abstract: The assembly, organization and function of the photosynthetic apparatus was investigated in the wild type and a chlorophyll (Chl) b-less mutant of the unicellular green alga Chlamydomonas reinhardtii, generated via DNA insertional mutagenesis. Comparative analyses were undertaken with cells grown photoheterotrophically (acetate), photomixotrophically (acetate and HCO3-) or photoautotrophically (HCO3-). It is shown that lack of Chl b diminished the photosystem-II (PSII) functional Chl antenna size from 320 Chl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 43 publications
(60 reference statements)
5
76
0
1
Order By: Relevance
“…This was already shown earlier (Polle et al, 2000), and similar results were obtained for another chlorophyll b-less mutant of C. reinhardtii, cbn1-113 (Park and Hoober, 1997). However, these data differ from those of higher plants, in which disruption of the chlorophyll a oxygenase gene in Arabidopsis does not eliminate the expression of the LHCP genes but leads to a complete loss of LHCPs (Espineda et al, 1999;J.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This was already shown earlier (Polle et al, 2000), and similar results were obtained for another chlorophyll b-less mutant of C. reinhardtii, cbn1-113 (Park and Hoober, 1997). However, these data differ from those of higher plants, in which disruption of the chlorophyll a oxygenase gene in Arabidopsis does not eliminate the expression of the LHCP genes but leads to a complete loss of LHCPs (Espineda et al, 1999;J.…”
Section: Discussionsupporting
confidence: 83%
“…Because we detected a higher expression rate of LHCPs in Arabidopsis than in C. reinhardtii, the difference might result from a faster degradation of nonfunctional LHCPs in higher plants (data not shown). Spectroscopic studies of cbs3 however showed that the PSII antenna is functional (Polle et al, 2000). The presence of antenna chlorophyll molecules remains to be clarified, but from our data, it is unlikely that PSII contains LHCPs in cbs3.…”
Section: Discussionmentioning
confidence: 59%
“…(a) Growth of the algae Chlamydomonas reinhardtii strains CC503, TLA1 overexpressing lines OE1, OE2 and OE3, TLA1 RNAi transformants Ri6, Ri8 and Ri9 and the chlorophylldeficient mutant tla1 were grown to the mid-exponential growth phase either in Tris-acetate-phosphate (TAP), pH 7.4 [29,30], or in modified minimal media containing 40 mM Tris-HCl, pH 7.4, supplemented with 25 mM sodium bicarbonate (TBP medium [31]) in culture flasks at 258C under continuous illumination of 150-300 mmol photons m 22 s 21 provided by coolwhite fluorescent lamps. The cultures were stirred continuously to ensure a uniform illumination of the cells and to prevent settling.…”
Section: Methodsmentioning
confidence: 99%
“…Chlorophylls a and b are indispensable for the stabilization of LHC proteins in land plants (Plumley and Schmidt 1995) and Chlamydomonas reinhardtii (Polle et al 2000). Indeed, the LHCII trimer is absent in the Arabidopsis ch1 mutant, which does not accumulate chlorophyll b due to mutation of the chlorophyll a oxygenase (CAO) gene (Espineda et al 1999;Tanaka et al 1998).…”
Section: Introductionmentioning
confidence: 99%